Antisense Oligonucleotide- and CRISPR-Cas9-Mediated Rescue of mRNA Splicing for a Deep Intronic CLRN1 Mutation - Anna-Lena Panagiotopoulos; Nina Karguth; Marina Pavlou; Sybille Böhm; Gilles Gasparoni; Jörn Walter; Alexander Graf; Helmut Blum; Martin Biel; Lisa Maria Riedmayr; Elvir Becirovic (Elsevier, 2020)
Mutations in CLRN1 cause Usher syndrome (USH) type III (USH3A), a disease characterized by progressive hearing impairment, retinitis pigmentosa, and vestibular dysfunction. Due to the lack of appropriate disease models, no efficient therapy for retinitis pigmentosa in USH patients exists so far. In addition, given the yet undefined functional role and expression of the different CLRN1 splice isoforms in the retina, non-causative therapies such as gene supplementation are unsuitable at this stage. In this study, we focused on the recently identified deep intronic c.254-649T>G CLRN1 splicing mutation and aimed to establish two causative treatment approaches: CRISPR-Cas9-mediated excision of the mutated intronic region and antisense oligonucleotide (AON)-mediated correction of mRNA splicing. The therapeutic potential of these approaches was validated in different cell types transiently or stably expressing CLRN1 minigenes. Both approaches led to substantial correction of the splice defect. Surprisingly, however, no synergistic effect was detected when combining both methods. Finally, the injection of naked AONs into mice expressing the mutant CLRN1 minigene in the retina also led to a significant splice rescue. We propose that both AONs and CRISPR-Cas9 are suitable strategies to initiate advanced preclinical studies for treatment of USH3A patients.